Do We Have Clinical Equipoise (or Uncertainty) About How Much Protein to Provide to Critically Ill Patients?. (7th June 2019) - Patel, Jayshil J.; Rice, Todd; Compher, Charlene; Heyland, Daren K.
Abstract: The current recommendation for protein dose in critically ill patients is 1.2–2.0 g/kg/d. Despite this recommendation, there is significant variation in the amount of protein prescribed and delivered worldwide. We contend clinical equipoise, or a state of genuine uncertainty about 2 (dosing) strategies, exists because guideline‐based recommendations for protein dose in critically ill patients are rooted in a weak evidentiary base, leaving the clinician with no good basis for choosing a lower or higher protein dose. We outline evidence for and against high protein dose and introduce a pragmatic, registry‐based, multicenter, randomized controlled trial, known as EFFORT, which aims to resolve the high vs low protein dose controversy.